2018
DOI: 10.1103/physrevlett.121.106801
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Zigzag Wigner Crystal in Confinement-Tunable Quantum Wires

Abstract: The existence of Wigner crystallization, one of the most significant hallmarks of strong electron correlations, has to date only been definitively observed in two-dimensional systems. In one-dimensional (1D) quantum wires Wigner crystals correspond to regularly spaced electrons; however, weakening the confinement and allowing the electrons to relax in a second dimension is predicted to lead to the formation of a new ground state constituting a zigzag chain with nontrivial spin phases and properties. Here we re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…[4][5][6][7][8][9] Of these, the 0.7(2e 2 /h) conductance anomaly, a plateau appearing just below the first conductance plateau, has been extensively investigated with considerable discussion on its origin, and this effect was linked to the intrinsic spin polarization within the 1D system by means of transverse electron focusing. [10][11][12] There have been various theoretical proposals on the possibility of nonmagnetic fractional conductance plateaux (below e 2 /h) in both 2D and 1D systems analogous to the fractional quantum Hall effect (FQHE). 13 I nt h eF Q H E ,t h ef r a c t i o n a l i z a t i o ni sp r i n c i p a l l yi nt h e form of odd-denominator fractions as a result of Coulomb interaction among electrons occupying the lowest Landau levels in the 2D system.…”
Section: Takedownmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Of these, the 0.7(2e 2 /h) conductance anomaly, a plateau appearing just below the first conductance plateau, has been extensively investigated with considerable discussion on its origin, and this effect was linked to the intrinsic spin polarization within the 1D system by means of transverse electron focusing. [10][11][12] There have been various theoretical proposals on the possibility of nonmagnetic fractional conductance plateaux (below e 2 /h) in both 2D and 1D systems analogous to the fractional quantum Hall effect (FQHE). 13 I nt h eF Q H E ,t h ef r a c t i o n a l i z a t i o ni sp r i n c i p a l l yi nt h e form of odd-denominator fractions as a result of Coulomb interaction among electrons occupying the lowest Landau levels in the 2D system.…”
Section: Takedownmentioning
confidence: 99%
“…6,7 It has been shown that the theoretically predicted 1D Wigner crystallization can not only be observed experimentally using the conductance measurement but also be imaged as two separate charge densities using transverse electron focusing. 10 This phase is very sensitive to the confinement potential and changes in the kinetic energy of the relaxed electrons. One way to modulate the confinement, and hence the wavefunction of weakly confined electrons, is to alter the symmetry of the confinement potential by applying an offset to one of the split gates.…”
Section: Takedownmentioning
confidence: 99%
“…Alhough this localized state could result from disorder in the potential of the QPC channel, it could also correspond to a spontaneously localized charge. Indeed, several evidences for the existence of bound states in QPCs near pinch-off have been reported [39,[52][53][54][55][56]. Such bounds states have been predicted to spontaneously form in QPCs by several numerical studies [51,[57][58][59][60], as a consequence of e-e interactions.…”
Section: Discussionmentioning
confidence: 98%
“…Известно также, что при ослаблении ограничивающего потенциала или увеличении концентрации электронов в вигнеровском кристалле происходит фазовый переход " струна−зигзаг" [22,23], который регистрируется в измерениях кондактанса в виде удвоения ступеней квантования кондактанса. Формирование двухрядного транспорта было наглядно показано в экспериментах по поперечной магнитной электронной фокусировке [24,25]. Однако в перечисленных работах речь не идет о независимом квантовании кондактанса отдельных каналов.…”
Section: Introductionunclassified